2017
DOI: 10.1038/s41598-017-08561-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of disulfide bridges and backbone connectivity on water sorption by protein matrices

Abstract: Understanding the water sorption behavior of protein powders is important in applications such as the preservation of protein-based pharmaceuticals. Most globular proteins exhibit a characteristic sigmoidal water adsorption isotherm at ambient conditions. However, it is not well understood how water sorption behavior is influenced by intrinsic factors that are related to structural properties of proteins. We investigate computationally how structural constraints on proteins influence the water sorption isother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…As the protein becomes more flexible, its RMSD increases, and is accompanied by a concomitant increase in Δ G . Our finding that a rigid protein is hydrated more favorably is also consistent with the work of Debenedetti and co-workers, who demonstrated that the thermodynamic drive for water sorption by protein crystals increases when the rigidity of the proteins in the crystal is enhanced, either artificially or physically via disulfide bonds. , …”
Section: The Role Of Protein Flexibilitysupporting
confidence: 92%
See 3 more Smart Citations
“…As the protein becomes more flexible, its RMSD increases, and is accompanied by a concomitant increase in Δ G . Our finding that a rigid protein is hydrated more favorably is also consistent with the work of Debenedetti and co-workers, who demonstrated that the thermodynamic drive for water sorption by protein crystals increases when the rigidity of the proteins in the crystal is enhanced, either artificially or physically via disulfide bonds. , …”
Section: The Role Of Protein Flexibilitysupporting
confidence: 92%
“…We find that a protein can be hydrated more favorably by enhancing its rigidity; for example, by engineering it to have a higher content of rigidifying residues, like proline, a high concentration of strong interactions, like salt bridges and disulfide bonds, ,, or through chemical cross-linking. Conversely, enhancing protein flexibility would serve to lower its propensity to remain hydrated, and in principle, it could not only lower protein solubility, but also be used to trigger protein assemblies. Intraprotein interactions, such as disulfide bonds or salt bridges, are also used to stabilize the folded state of a protein. ,, In addition to stabilizing the folded state directly, our findings suggest that such favorable interactions ought to also favor the folded state indirectly through their role in enhancing protein rigidity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[60][61] In desorption mode, the bound water molecules keep the polymer chains apart, and the contractive forces are not sufficient to force the water molecules from the swollen structure as the water vapor pressure decreases, resulting in higher water content compared to that in sorption mode. The large sorption hysteresis was also found in weak polyelectrolytes, and other amorphous materials (e.g., protein powder), [62][63][64] in which case the sorption hysteresis was attributed to the polymer's resistance to plasticization by water (i.e., stiffer chains) due to its higher shear modulus and the larger stress relaxation time consequently hampers the response to RH changes. 65 While water content (λ) is used to describe the local hydration of ionomer moieties, water volume fraction,𝜙 𝑤 , is a better representation of the network-level properties.…”
Section: Sorption Hysteresis and Swellingmentioning
confidence: 95%